A bifurcated waveguide problem - Büyükaksoy, Alinur; Polat, Burak (Istanbul Technical University, 1999)
We consider the diffraction of the dominant mode in a parallel-plate waveguide with hard boundaries which is incident on a centered soft-hard half-plane. By using the Fourier transform technique in conjunction with the Mode Matching method, the related boundary value problem is formulated as a modified Wiener-Hopf equation. The solution of the latter, which contains infinitely many constants, is found by solving numerically an infinite set of linear algebraic equations. © Springer-Verlag 1999. © 2020 Elsevier B.V., All rights reserved.
Keywords: Bifurcated waveguide; Mixed boundary value problems; Mode matching method; Propagation; Wiener-Hopf technique